Implementing a psychological skills training program in high school volleyball athletes - Fulgham, A.
Most of the research on psychological skills training has compared elite athletes to non-elite athletes, and how they use these skills. Very few studies have examined whether high school athletes would be able to benefit from these same psychological skills if simplified. The purpose of this research was to see if high school athletes were able to benefit from the Psychological Skills Training Program where imagery and goal setting were implemented. Eleven participants from the female varsity volleyball team at a local high school were assigned to either a " Psychology Skills" group or a "No Training" group. Throughout the study, participants completed a weekly pre- / post questionnaire and logbook examining the use and effect of their assigned training program. Separate (2x2) Analyses of Variance indicated a significant main effect on the coach`s effectiveness, the participants` confidence in the coach to motivate the team, participants` confidence, and the attitude of the participants. The benefits of a Psychological Skills Training program for high school athletes appear to be consistent with the benefit accrued from more elite athletes.